OPERATION OF ELECTRIC MACHINES. TESTING, STANDARDS AND SIZE OF TRANSFORMERS AFTER OVERHAUL. - Usmonov Inomjon Isroilovich; Mirzayev Islambek Umarali ugli; Bakhriddinova Dilnora Sharifjon kizi; Khusanova Sarvinoz Alisher kizi (Scholar Express Journals, 2023)
This article, we will discuss the operation of electric machines, testing and standards, and the size of transformers after overhaul
Keywords: Electric machines; Operation; Testing; Standards